IFNγ-INDUCED KINURENINE PRODUCTION AND INDOLAMINE 2,3-DIOXYGENASE GENE EXPRESSION IN PSORIASIS - D. A. Kaut; R. S. Yamidanov; S. V. Sadovnikov; O. M. Kapuler; V. A. Vakhitov; S. V. Sibiryak (Медицинская иммунология)
Abstract. An alternative pathway of L-tryptophan biotransformation is provided by the indolamine 2,3-dioxygenase (INDO), and it results into synthesis of kynurenine and other «distal» metabolites, playing a pivotal role in immunoregulation and down-regulation of immune inflammation. PBMCs from healthy volunteers, patients with progressive vulgar psoriasis (PASI (M±SD) = 25.6±16.6), or patients with psoriatic arthropathy (PASI = 40.3±24.5). The cells were incubated for 24 hrs with IFNγ (500 IU/ml, stimulated cultures) or without cytokine (control cultures). Distinct abnormalities in spontaneous and induced kynurenine production (colorimetric method) and INDO expression (semi-quantitative RT-PCR) were observed in psoriasis and psoriatic arthritis. PBMCs from psoriatic patients, in comparison with healthy donors, were characterized with slightly increased spontaneous kynurenine production, spontaneous and IFNγ-induced INDO expression, while IFNγ-induced kynurenine levels were approximately two times higher. In psoriatic arthritis, spontaneous kynurenine production and INDO expression were significantly lower than in donor’s PBMC, whereas IFNγ-induced kynurenine production were the same as for the donors, while IFNγ – induced INDO expression was markedly increased.